Regionalna identiteta v Sloveniji - Kosi, Danilo (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The paper is dealing with various aspects of regional identity. Regional identities are established and maintained with social functioning, passing through different spheres of social activities. All these activities are present in spatially integrated areas, causing differentiation of space and creating the sense of common regional belonging. The purpose of this article is to present the causes of regional identity and its consequences in spatial structures. One of the consequences could be the appearance of identity regions.
Keywords: geografija; geography; regije; regionalna identiteta; Slovenia; Slovenija